PENGEMBANGAN BAHAN AJAR KALKULUS BERBASIS MASALAH DENGAN BANTUAN SOFTWARE GRAPMATICA PADA MATERI SISTEM KOORDINAT KUTUB, TABUNG DAN BOLA - I ilmadi; Nina Valentika; Gerry Sastro (Universitas Muhammadiyah Semarang, 2020)
The purpose of this study is to design teaching materials for Problem-based Calculus with the help of Grapmatica software in the Polar Coordinate System, Savings and Ball material, these teaching materials are implemented through valid, practical and effective learning modules. The methodology used in this study combines Plomp model research design with Gravemeijer & Cobb models. The stages of design research in this study were the preliminary research phase, the preparation of the experiment, the prototype development phase, the implementation of the experiment, the restrosfective analysis, and the assessment phase. Data analysis techniques in this research are descriptive statistics and descriptive techniques, which describe the validity, practicality and effectiveness of learning flow design through problem-based learning modules. Data collection instruments used: tests, observation sheets, interview sheets, questionnaires and field notes. The research subjects were 6th semester students of Mathematics Study Program FMIPA Univ. Pamulang who attended the Advanced Calculus lecture.The results of the validity data analysis show that the learning flow design is implemented through modules; Problem based learning that is produced has met the valid criteria. Said to be valid because it meets the characteristics of validity both in terms of content and construct. The contents of the learning design through the learning flow that are implemented in the learning module are guided by principles and are problem based. The context of the problems contained in the learning design is adapted to the context of student life and can bring students to do the mathematical process. The process of mathematics is one of the main focuses of this learning design, in order to train students to construct their own knowledge based on initial knowledge or experience. The learning flow design implemented through the learning module is practical because it is easy to use and understand, the allocation of time determined is efficient, interesting and contributes to learning in the Polar Coordinate System, Savings and Spheres. The learning flow design implemented through the learning module has also been effective because the use of this learning design has a potential impact on students' reasoning abilities on the topic of Polar, Savings and Ball Coordinate Systems. Based on these results, it can be concluded that the learning design of the topic of the Polar Coordinate System, Savings and Ball using Problem Based Calculus teaching materials with the help of grapmatica software on the material coordinate system of the lid, tubes and balls has been produced can be declared valid, practical and effective